Insulin Blocks Glutamate-Induced Neurotoxicity in Differentiated SH-SY5Y Neuronal Cells - Madhavan Nampoothiri; Neetinkumar D. Reddy; Jessy John; Nitesh Kumar; Gopalan Kutty Nampurath; Mallikarjuna Rao Chamallamudi (Behavioural Neurology)
Insulin is a cytokine which promotes cell growth. Recently, a few published reports on insulin in different cell lines support the antiapoptotic effect of insulin. But the reports fail to explain the role of insulin in modulating glutamate-mediated neuronal cell death through excitotoxicity. Thus, we examined the neuroprotective effect of insulin on glutamate-induced toxicity on differentiated SH-SY5Y neuronal cells. Changes in cell viability were measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide (MTT) based assay, while apoptotic damage was detected by acridine orange/ethidium bromide and Hoechst staining. Intracellular reactive oxygen species (ROS) accumulation and morphological alterations were also measured. Treatment with glutamate induced apoptosis, elevated ROS levels and caused damage to neurons. Insulin was able to attenuate the glutamate-induced excitotoxic damage to neuronal cells.